SENGKETA LINGKUNGAN HIDUP DALAM PERSPEKTIF HUKUM PERDATA LINGKUNGAN - Indah Sari (UNIVERSITAS DIRGANTARA MARSEKAL SURYADARMA, 2016)
The growth of development and demands in people’s life have brought us problem of environmental disputes. While there are disputes or quarrels between individuals, corporations, and state or government; the scoop of the disputes include private law, public law, administrative law, and international law. This writing is focused on environmental disputes based on private law, and also on the mechanism of dispute solutions –both through litigational or non-litigational mechanism. In litigational mechanism, people could submit a lawsuit for an act against law comitted by others based on article 1365 KUH Perdata. In non-litigational mechanism, they need to find alternative dispute solution through processes of negotiation, mediation, consiliation, even arbitrage. Both mechanism, basically, try to make up for damage by compensation and also to recover environmental detriment for a better condition.